Seal the Deal: Bargaining Positions, Institutional Design, and the Duration of Preferential Trade Negotiations. Issue 5 (3rd September 2018) - Lechner, Lisa; Wüthrich, Simon
ABSTRACT: Multilateral negotiations at the World Trade Organization have stalled. This has contributed to a steep rise in preferential trade agreements (PTAs). At the same time, negotiations for PTAs have not always proven quick and painless: While some treaties are sealed within a few months or days only, other agreements are preceded by protracted bargaining processes in trade and trade-related issue areas. In this article, we provide a theoretical explanation for this empirical variation. More specifically, we argue that PTA negotiations take longer the greater the distance between the prospective partners' initial bargaining positions. Moreover, we contend that negotiation processes become more protracted the higher the relative ambition of the prospective PTA. Due to the limited links to the domestic political arena in autocracies, we expect this latter effect to play out for groups of democratic bargaining partners only. We test these two hypotheses for 198 preferential trade negotiations using novel measures for bargaining templates and the ambition of PTA clauses. In our two-stage survival models, we find support for our argument. In line with qualitative evidence from recent preferential trade initiatives, our models indicate that services, investment and intellectual property rights are particularly sticky agenda items for democratic leaders at the international bargaining table.